Generation of diverse high-affinity human monoclonal antibodies by repertoire cloning. - Persson, M A (1991)
Combinatorial libraries of antibody heavy and light chains derived from the peripheral blood lymphocytes of an individual immunized with tetanus toxoid have been expressed in Escherichia coli by using phage lambda vectors. Screening of the libraries allowed identification of a large number of human monoclonal Fab fragments specific for tetanus toxoid. Initial studies suggested considerable sequence diversity in these antibodies. The method should allow the generation of many human monoclonal antibodies of interest and the dissection of human humoral immune responses.